RETRACTED: Impact of environment on hotel customer satisfaction in Southeast Asia: A study of online booking site reviews - Ding, Cuicui; Guo, Qingran; Rehman, Alam; Zeeshan, Muhammad (Frontiers in Environmental Science, 2022)
This paper empirically analyzes the effect of environment on customer satisfaction in online hotel booking for tourists in Southeast Asian countries. Customer reviewers are used for analysis by applying the logistic regression method for the estimations. The empirical outcomes reveal that environment could significantly influence customer satisfaction, which implies tourists likely to maximize their satisfaction by choosing destinations providing a good environment. In addition, rental price, hotel location and service quality could also increase customer satisfaction. The web-based customer reviews can potentially affect the booking decision of the tourists and the reviewer’s comments carefully evaluate while making booking decisions. Hotel authorities in Southeast Asian countries can improve the hoteling service by adopting renewable energy resources of energy which may increase the booking intention. Furthermore, the customer’s feedback is an important factor and hotel authorities may improve the hotel services by considering the reviewer's comments.